Soybeans in Mato Grosso: Production Analysis and Crop Estimation Model - André Ximenes de Melo; Sonia A. Beato Ximenes de Melo; Antônio Cézare de Araújo Giansante; Denis Donaire (Gestão & Regionalidade)
The present article aims to clarify the transformations that have occurred since the 1970s in the soybean production chain, having as a spatial clipping the state of Mato Grosso, which has been receiving contributions of technological innovations in the modernization of the agricultural sector, and becoming the first producer of Brazil's soybean, with 10% of all world production. What will be questioned in this article is: what are the qualities and potentialities to be used by soybean crops in the state of Mato Grosso? World soybean production is 3.36 108 t, occupying 124 M ha in plantation. The United States and Brazil account for 70% of world production, Argentina produces around 15%. Mato Grosso has a productivity of 3,367 kg ha –1, 25% higher than the world average. The research was exploratory, using secondary data provided by different institutions, which were analyzed using linear regression. It was found that productivity grew continuously during the period studied, and that the 20 largest producers are hegemonic in production, but they are seeing a reduction in participation from 73% to 59%, and that the area expected for 2019 is close to 10 M ha.